The novel sRNA s015 improves nisin yield by increasing acid tolerance of Lactococcus lactis F44 - Qi, Jiakun; Caiyin, Qinggele; Wu, Hao; Tian, Kairen; Wang, Binbin; Li, Yanni; Qiao, Jianjun (Applied microbiology and biotechnology, 2017)
Nisin, a polycyclic antibacterial peptide produced by Lactococcus lactis , is stable at low pH. Improving the acid tolerance of L. lactis could thus enhance nisin yield. Small non-coding RNAs (sRNAs) play essential roles in acid tolerance by regulating their target mRNAs at the post-transcriptional level. In this study, a novel sRNA, s015, was identified in L. lactis F44 via the use of RNA sequencing, qRT-PCR analysis, and Northern blotting. s015 improved the acid tolerance of L. lactis and boosted nisin yield at low pH. In silico predictions enabled us to construct a library of possible s015 target mRNAs. Statistical analysis and validation suggested that s015 contains a highly conserved region (5′-GAAAAAAAC-3′) that likely encompasses the regulatory core of the sRNA. atpG , busAB , cysD , ilvB , tcsR , ung , yudD , and ywdA were verified as direct targets of s015, and the interactions between s015 and its target genes were elucidated. This work provided new insight into the adaptation mechanism of L. lactis under acid stress .